Terapia fotodynamiczna w leczeniu neowaskularyzacji odnaczyniówkowej towarzyszącej pasmom naczyniastym – opis przypadku - Figurska, Małgorzata (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
The aim of this paper is to present the effects of photodynamic therapy for treatment of bilateral macular choroidal neovascularization in angioid streaks during 16 months period. 50 years old man has one PDT in the right eye and three in the left eye. In the left eye conversion from choroidal neovascular membrane (CNV) to a fibrous disciform lesion following photodynamic therapy, was observed. In the right eye vision decreased from 1.0 to 0.2, but the leakage was minimal and stabilization of CNV size after the progression was noted.